PENERAPAN LAPORAN KEUANGAN DIGITAL MENGGUNAKAN APLIKASI BUKUKAS PADA UMKM WARUNG MAK YANTO - Fauzi Fauzi; Novi Chandra Saputra; Annisa Nur Fadila; Arif Akhmad Maulana; Dianti Aprilia; Putri Anggreni; Syarifah Syifa Azzahra (Bajang Institute, 2023)
In today's digital era, there are still many MSME that do manual recording. The importance of digital financial literacy through bookkeeping applications for MSME can help them record their financial transactions and make it easier to recap sales of products sold through the Cash Book application. The purpose of community service for MSME is to record financial transactions using the BukuKas application in a simple way. The method used is service learning, starting from the preparation stage, the dedication stage and reflection. The results of this activity are MSME players can use the Cash Book application, can operate transactions in the Cash Book, and can find out the cost of goods sold, make financial records and prepare financial reports.